ความสัมพันธ์ระหว่างองค์ประกอบทางเคมีและสารหอม 2-แอซีติล-1-ไพรโรลีน และการเปลี่ยนแปลงของสมบัติเพสติงของข้าวพันธุ์ขาวดอกมะลิ 105 ระหว่างการเก็บรักษา - บัณฑิต ลีฬหรัตนรักษ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2005)
To study the effect of 42 different areas at Tungkula on chemical compositions and 2-acetyl-1-pyrroline (2-AP) of Khao Dawk Mali 105 (KDML 105) and the relationship between chemical composition and 2-AP content in the rice during storage. In addition, the changes of pasting properties and protein pattern in the rice stored at room temperature were also investigated. The different fields affected 2-AP content and chemical compositions (moisture, crude fat, amylose and protein content) of the rice significantly (p<=0.05). Pearson correlation analysis between 2-AP and the chemical composition indicated positive correlation between amylose and 2-AP content (p<=0.05). During storage, 2-AP and moisture contents of the rice decreased while amylose content increased (p<=0.05). Pearson correlation analysis showed negative correlated of 2-AP content with protein and amylose but positively correlated with bound lipid content significantly (p<=0.05). Pasting property of the rice by RVA indicated that aging caused peakviscosity, peak time and breakdown decreased while setback values increased significantly (p<=0.05). Adding beta-mercaptoethanol increased peak viscosity and breakdown but decreased setback during storage significantly (p<=0.05). If free lipid in the rice were removed, peak viscosity increased significantly (p<=0.05). On the other hand, when both free and bound lipids were removed from the rice, peak viscosity decreased significantly (p<=0.05). During storage at room temperature for eight months, hardness, cohesiveness and chewiness of the rice increased whilst adhesiveness decreased significantly (p<=0.05) and molecular size of rice protein increased over time.